Global analysis of uncapped mRNA changes under drought stress and microRNA-dependent endonucleolytic cleavages in foxtail millet. Issue 1 (December 2015) - Yi, Fei; Chen, Jian; Yu, Jingjuan
Abstract Background mRNA degradation plays an important role in the determination of mRNA abundance and can quickly regulate gene expression. The production of uncapped mRNAs, an important mechanism of mRNA degradation, can be initiated by decapping enzymes, endonucleases or small RNAs such as microRNAs (miRNAs). Little is known, however, about the role of uncapped mRNAs in plants under environmental stress. Results Using a novel approach called parallel analysis of RNA ends (PARE), we performed a global study of uncapped mRNAs under drought stress in foxtail millet (Setaria italica [L.] P. Beauv.). When both gene degradation (PARE) and gene transcription (RNA-sequencing) data were considered, four types of mRNA decay patterns were identified under drought stress. In addition, 385 miRNA–target interactions were identified in the PARE data using PAREsnip. The PARE analysis also suggested that two miRNA hairpin processing mechanisms—loop-last and loop-first processing—operate in foxtail millet, with both miR319 and miR156 gene families undergoing precise processing via the unusual loop-first mechanism. Finally, we found 11 C4 photosynthesis-related enzymes encoded by drought-responsive genes. Conclusions We performed a global analysis of mRNA degradation under drought stress and uncovered diverse drought-response mechanisms in foxtail millet. This information will deepen our understanding of mRNA expression under stressful environmental conditions in gramineous plants. In addition, PARE analysis identified many miRNA targets and revealed miRNA-precursor processing modes in foxtail millet.